Internalization of the Paris Agreement in Indonesia’s First Nationally Determined Contributions (NDCs) (2015–2022) - Nurngaini, Dewi; Rohma, Masitoh Nur (Insignia: Journal of International Relations, 2025)
Abstract Climate change is a global challenge that affects various sectors and serves as the foundation for the establishment of the international Paris Agreement, which was adopted through the Conference of Parties (COP) under the United Nations Framework Convention on Climate Change (UNFCCC). This agreement was strongly advocated by Ban Ki-Moon, Secretary-General of the United Nations from 2007 to 2016. As one of the countries vulnerable to the impacts of climate change, Indonesia has decided to ratify the Paris Agreement and has made serious efforts to achieve its Nationally Determined Contributions (NDC) target, aiming to reduce greenhouse gas (GHG) emissions. These efforts have yielded positive results, with Indonesia gradually surpassing its emission reduction targets as reported by the Ministry of Environment and Forestry (MoEF) in 2022. This study examines the development of the Paris Agreement as a new international norm that influences Indonesia’s policies in addressing climate change impacts through the norm life cycle framework. This framework consists of three stages: norm emergence, norm cascade, and internalization. In this context, the Paris Agreement is viewed as an international norm initiated by the norm entrepreneur Ban Ki-Moon, who successfully encouraged Indonesia to ratify and implement it at the national level. This success is reflected in the internalization of the Paris Agreement into legal instruments that strengthen Indonesia’s commitment to achieving its NDC targets. This research applies a qualitative analytical method, drawing on secondary sources such as official government and organizational reports, journal articles, books, and other relevant references. Keywords: Indonesia’s carbon emissions, international regime, norm life cycle, Paris Agreement Abstrak Perubahan iklim merupakan tantangan global yang memengaruhi berbagai sektor dan menjadi landasan lahirnya kesepakatan internasional Paris Agreement, yang disepakati melalui Conference of Parties (COP) di bawah naungan United Nations Framework Convention on Climate Change (UNFCCC). Kesepakatan ini mendapat dorongan kuat dari Sekretaris Jenderal Perserikatan Bangsa-Bangsa periode 2007–2016, Ban Ki-Moon. Sebagai salah satu negara yang rentan terhadap dampak perubahan iklim, Indonesia memutuskan untuk meratifikasi Paris Agreement dan berupaya secara serius mencapai target Nationally Determined Contributions (NDC) dalam menurunkan emisi gas rumah kaca (GRK). Upaya ini menunjukkan hasil positif, di mana Indonesia secara bertahap mampu melampaui target penurunan emisi sebagaimana dilaporkan Kementerian Lingkungan Hidup dan Kehutanan (KLHK) pada 2022. Penelitian ini menganalisis perkembangan Paris Agreement sebagai norma baru di tataran internasional yang memengaruhi kebijakan Indonesia dalam mengendalikan dampak perubahan iklim melalui kerangka norm life cycle. Kerangka ini mencakup tiga tahap, yakni norm emergence, norm cascade, dan internalization. Dalam konteks ini, Paris Agreement dipandang sebagai norma internasional yang digagas oleh norm entrepreneur Ban Ki-Moon, yang berhasil mendorong Indonesia untuk meratifikasi dan mengimplementasikannya di tingkat nasional. Keberhasilan tersebut tercermin dari proses internalisasi Paris Agreement ke dalam instrumen hukum yang memperkuat komitmen Indonesia dalam mencapai target NDC. Penelitian ini menggunakan metode analisis kualitatif dengan sumber data dari laporan resmi pemerintah atau organisasi, artikel jurnal, buku, maupun sumber sekunder lain yang relevan. Kata kunci: emisi karbon Indonesia, norm life cycle, Paris Agreement, rezim internasional